2012
DOI: 10.1084/jem.20111694
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resistance to JAK2 enzymatic inhibitors is overcome by HSP90 inhibition

Abstract: Hsp90 inhibition in B cell acute lymphoblastic leukemia overcomes resistance to JAK2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
175
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(191 citation statements)
references
References 55 publications
(88 reference statements)
13
175
2
1
Order By: Relevance
“…3A). Multiple JAK2 inhibitors have been previously reported to show similar results where they directly target JAK2 but increase or do not affect JAK2 phosphorylation levels (44,45). GinA markedly inhibited S6 phosphorylation dose-dependently in both EJ and HCT116 cells (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…3A). Multiple JAK2 inhibitors have been previously reported to show similar results where they directly target JAK2 but increase or do not affect JAK2 phosphorylation levels (44,45). GinA markedly inhibited S6 phosphorylation dose-dependently in both EJ and HCT116 cells (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Previous studies have also reported multiple JAK2 inhibitors that maintained or increased the phosphorylation levels of JAK2 (44,45). In addition, inhibitors for other kinases have been shown to not affect the phosphorylation levels of the target kinase, whereas the activity was inhibited by the compounds (51)(52)(53).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Hsp90 is a promising therapeutic target also in JAK-2 driven cancer, e.g., myeloproliferative neoplasms, B cell acute lymphoblastoid leukemia, including those with genetic resistance to JAK enzymatic inhibitors (122,123). Intriguingly, Hsp90 inhibitor-based antileukemia therapy may override de novo or acquired resistance of acute myelogenous leukemia cells to pan-histone deacetylase inhibitors (124).…”
Section: Combination Of Hsp90 Inhibitor With Second Therapymentioning
confidence: 99%
“…Indeed, in the same studies, cytotoxicity assays show that the cells having the resistant mutations were more sensitive than WT cells to HSP90 inhibition using AUY22. 101 Similarly, inhibition of HSP90 activity has also been shown to be effective in cases where cells are able to overcome Jak2 inhibition and sustain aberrant JAK/ STAT signaling by co-opting other kinases to trans-activate Jak2. 102 These examples, while not exhaustive, highlight the importance of HSP90 in the development and maintenance of many pathological states mediated by aberrant JAK/STAT signaling, including both solid and hematologic malignancies, 99 along with the therapeutic potential of pharmacological inhibition HSP90 as potential treatment for such malignancies.…”
Section: Jak Kinases and Chaperonesmentioning
confidence: 99%